2021
DOI: 10.1007/s10162-021-00821-3
|View full text |Cite
|
Sign up to set email alerts
|

Reweighting of Binaural Localization Cues in Bilateral Cochlear-Implant Listeners

Abstract: Normal-hearing (NH) listeners rely on two binaural cues, the interaural time (ITD) and level difference (ILD), for azimuthal sound localization. Cochlear-implant (CI) listeners, however, rely almost entirely on ILDs. One reason is that present-day clinical CI stimulation strategies do not convey salient ITD cues. But even when presenting ITDs under optimal conditions using a research interface, ITD sensitivity is lower in CI compared to NH listeners. Since it has recently been shown that NH listeners change th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Furthermore, recent studies have demonstrated that lateralization training can lead to a reweighting of binaural cues in normal hearing listeners (Kumpik et al 2019; Klingel et al 2021) and biCI users (Klingel and Laback 2022), such that the listeners rely more or less heavily on ILDs or ITDs respectively depending on which cue is more reliable or informative. This could be relevant for CI listeners, as they could similarly down-weight ITD cues if the ongoing stimulation with clinical processors does not transmit reliable, informative ITDs which would thus encourage a reliance exclusively on ILDs to the detriment of ITDs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, recent studies have demonstrated that lateralization training can lead to a reweighting of binaural cues in normal hearing listeners (Kumpik et al 2019; Klingel et al 2021) and biCI users (Klingel and Laback 2022), such that the listeners rely more or less heavily on ILDs or ITDs respectively depending on which cue is more reliable or informative. This could be relevant for CI listeners, as they could similarly down-weight ITD cues if the ongoing stimulation with clinical processors does not transmit reliable, informative ITDs which would thus encourage a reliance exclusively on ILDs to the detriment of ITDs.…”
Section: Discussionmentioning
confidence: 99%
“…The rats in these studies spent their entire lives before puberty without any auditory input, but, unlike human CI users, once they were implanted they were also never exposed to prolonged periods of stimulation with the uninformative and potentially misleading pulse timing ITDs that wearers of bilateral clinical speech processors will experience constantly. Note that recent studies have demonstrated that lateralization training can lead to a reweighting of binaural cues in normal hearing listeners [77; 78] and biCI users [79], such that the listeners rely more or less heavily on ILDs or ITDs, respectively, depending on which cue is more reliable or informative. The auditory pathway thus seems clearly capable of desensitizing to ITD cues if provided with prolonged stimulation that is bereft of informative ITDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many CI stimulation strategies encode ITDs only via the envelope of the stimulus waveform and, even when encoding ITDs via the pulse timing, CI listeners’ sensitivity pattern resembles that for envelope ITDs in acoustic hearing ( Bernstein & Trahiotis, 2002 ; Laback et al, 2007 ). In fact, binaural-cue reweighting has recently been observed in CI listeners when ITDs were encoded via the pulse timing of low-rate pulse trains ( Klingel & Laback, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rats in these studies spent their entire lives before puberty without any auditory input, but, unlike human CI users, once they were implanted they were also never exposed to prolonged periods of stimulation with the uninformative and potentially misleading pulse timing ITDs that wearers of bilateral clinical speech processors will experience constantly. Note that recent studies have demonstrated that lateralization training can lead to a reweighting of binaural cues in normal hearing listeners 86,87 and biCI users 88 , such that the listeners rely more or less heavily on ILDs or ITDs, respectively, depending on which cue is more reliable or informative. The auditory pathway thus seems clearly capable of desensitizing to ITD cues if provided with prolonged stimulation that is bereft of informative ITDs.…”
Section: Does the Place Of Stimulation Matter?mentioning
confidence: 99%